Special Issue dedicated to Professor M. Sapagovas 75th Anniversary NUMERICAL ANALYSIS FOR BOUNDARY VALUE PROBLEMS WITH NONLOCAL CONDITIONS. Guest Editors: Mifodijus Sapagovas, Regimantas Čiupaila, Artūras Štikonas. Preface. - Ivanauskas, Feliksas; Rutkauskas, Stasys (Nonlinear Analysis: Modelling and Control, 2014)
This Special Issue of Nonlinear Analysis: Modelling and Control is dedicated to Professor Mifodijus Sapagovas 75th Anniversary. Prof. Sapagovas is known as a progenitor of the researches of numerical analysis in Lithuania (see http://www.yrasalis.lt). The main interests of his investigations are the numerical methods in the theory of differential equations and the mathematical modeling as well. He has published on these subjects about 140 scientific articles and several scientific books and textbooks. The results obtained by Prof. Sapagovas in these areas are well known in many countries and are widely cited by many researches not only in mathematics but in the adjacent scientific branches, too.